Bacterial pneumonia as a result of mechanical ventilation in patients treated in intensive care units – epidemiological importance - Leszcz, Katarzyna; Słomka, Tomasz; Karwat, Irena Dorota; Sobieszczański, Jarosław (Polish Journal of Public Health, 2012)
Introduction. Ventilator-associated pneumonia (VAP) is among the most common hospital infections in an Intensive Care Unit (ICU). The most important risk factors of VAP are endotracheal catheterization and mechanical ventilation. Aim. The objective of the study was evaluation of the prevalence of ventilator-associated pneumonia, and determination of the type of microbiological agents in specimens collected from the bronchial tree. Material and methods. The study covered 42 patients: 59.5% of males and 40.5% of females, hospitalized in the Intensive Care Unit (ICU), in whom mechanical ventilation was applied. Airway secretion was grown on a solid agar medium: Columbia agar with 5% sheep blood, chocolate agar, McConkey and Sabouraud media. Identification of the bacterial strains grown was based on the determination of their biochemical properties, with the use of commercial assays (bio-Merieux): ID 32E and ID 32GN and tests ID 32 STAPH and API 20 STREP. Results. In the group of 42 patients who received mechanical ventilation (59.5% of the total number of hospitalized patients) VAP developed in 17 patients (40.5%). From the specimens 30 (34.9%) strains of Gram-negative rods, 19 (22%) strains of Gram-positive cocci, and 13 (15.1%) fungi were grown. The largest number of strains was isolated in patients who received artificial ventilation until day 20 of hospitalization. Conclusions. The microorganisms most often isolated from the upper airways were Gram-negative rods; patients admitted to ICU from other wards were colonized with bacterial flora conveyed with them from the original ward; the duration of artificial ventilation increases the risk of occurrence of ventilator-associated pneumonia.